Reframing Human Trafficking: Indonesia’s Diplomacy in Tackling Chinese Mail-Order Bride Cases - Luthfiyani Nurul Jannah; Asep Setiawan; Usni Usni; Debbie Affianty (Publikasi Indonesia, 2024)
The phenomenon of Chinese mail-order brides in Indonesia gained prominence in the 1980s and resurfaced in 2017, particularly affecting regions like West Kalimantan. This research aims to examine Indonesia’s diplomatic strategies in addressing Chinese mail-order brides as human trafficking cases (TPPO) from 2018 to 2021, focusing on engagements between the Indonesian Minister of Foreign Affairs and the Chinese Government. Theoretical frameworks of diplomacy, humanitarian diplomacy, and human security provide the analytical lens for this study. The study employs a qualitative research method, leveraging a comprehensive literature review of official documents, academic sources, and credible news articles. The research findings reveal that poverty, limited education, parental influence, and scarce employment opportunities contribute to the prevalence of mail-order brides. Additionally, cultural perceptions and aspirations for an improved life exacerbate the issue. The Indonesian government, through bilateral diplomacy, has made significant efforts, such as negotiating victim repatriation and enhancing law enforcement collaborations with China. Notable successes include framing mail-order bride cases as TPPO, which facilitated victim repatriation. NGOs like the Indonesian Migrant Workers' Union (SBMI) have played essential roles in advocacy and preventive measures. Despite these efforts, challenges remain, such as differing cultural perspectives between Indonesia and China and regulatory inconsistencies. Governmental complicity and inadequate documentation have further complicated diplomatic resolutions. The research highlights that Indonesia’s strategic reframing of mail-order bride cases as human trafficking crimes enhances international cooperation and offers policy innovation for addressing human rights violations.